Free and bound phenols from Cymbopogon citratus mitigated hepatocellular injury in streptozotocin-induced type 1 diabetic male rats via decrease in oxidative stress, inflammation, and other risk markers - John Adeolu Falode; Temidayo Blessing Olofinlade; Gbenga Samuel Fayeun; Akinwunmi Oluwaseun Adeoye; Fisayo Abraham Bamisaye; Olawale R. Ajuwon; Tajudeen Olabisi Obafemi (Elsevier, 2023)
Background/Aim: Diabetes mellitus is a debilitating disease still prevailing in the developing world. This study aimed to examine the protective potentials of Cymbopogon citratus extracts (crude (CCC), free (CFP), and bound phenol (CBP) fractions), in streptozotocin (STZ)-induced type 1 diabetic male rats. Methods: Forty-five (45) animals of about 3-4 months were used for the study. About forty animals were induced with STZ. After induction and confirmation of diabetes, animals were grouped (five animals per group) into nine groups; group 1 (Control), group 2 received 50 mg/kg body weight (bw) (STZ). Groups 3, 4 and 5 were healthy animals and received C. citratus extracts (200 mg/kg bw CCC, 100 mg/kg bw CFP, and 100 mg/kg bw CBP) respectively; while groups 6 - 9 were diabetic group (induced with STZ) and later treated with C. citratus extracts (200 mg/kg bw CCC, 100 mg/kg bw CFP, 100 mg/kg bw CBP, and metformin (200 mg/kg bw) respectively for 14 days. Then, the animals were euthanized, blood/serum was collected, liver samples were collected and divided into two; for biochemical and histopathological studies. Liver biomarkers (ALT, AST, ALP, GGT), fructose-1,6-bisphosphatase, hexokinase, antioxidant enzymes (SOD, CAT, and GST) activities, albumin, bilirubin, hepatic glucose, GSH, MDA, pro-and anti-inflammatory cytokines concentrations, were estimated using standard protocols. Results: Our results revealed that C. citratus extracts counteracted the deleterious effects of type 1 diabetes induction with STZ by optimizing the liver biomarkers, antioxidants enzymes, MDA and GSH levels, reducing the levels of pro-inflammatory cytokines and increasing anti-inflammatory. Conclusion: Our results correlated with previous researches; the free phenols fraction revealed brilliant results above others. These suggested that C. citratus could serve as an alternative therapy in ameliorating liver complications linked to oxidative damage and inflammation in STZ-induced type-1 diabetes.